Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1080/01431161.2015.1014971
|View full text |Cite
|
Sign up to set email alerts
|

Using hyperspectral radiometry to predict the green leaf area index of turfgrass

Abstract: The green leaf area index (LAI) is an important indicator of the photosynthetic capacity of turfgrass canopies. The measurement of LAI is typically destructive and requires large plots to allow for multiple sampling dates. Hyperspectral radiometry may provide a rapid, non-destructive means for estimating LAI. Our objectives were to: (1) evaluate the utility of hyperspectral radiometry to predict the LAI of Kentucky bluegrass (Poa Pratensis L.); and (2) determine regions of the spectrum that provide the best LA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Advancements in irrigation system technologies along with the development and implementation of best management practices have drastically improved the capacity for water savings while maintaining turfgrass quality demands. Time-domain reflectometer (TDR) soil moisture sensors (SMS) [90], remote sensing of soil moisture stress through the normalized difference vegetation index (NDVI) [91], highly sensitive imagederived canopy indices [92] such as water band index (WBI), a simple visible vegetation index called green-to-red ratio index (GRI) [93], optical signature of leaves including hyperspectral radiometer [94,95] and other systems have been used to measure volumetric water content (VWC) or estimating moisture stress for irrigation scheduling strategies in turfgrass system. Use of soil moisture sensors was found to reduce water usage by 39% as compared to using historical ET data [96].…”
Section: Irrigation Application Methods and Schedulingmentioning
confidence: 99%
See 1 more Smart Citation
“…Advancements in irrigation system technologies along with the development and implementation of best management practices have drastically improved the capacity for water savings while maintaining turfgrass quality demands. Time-domain reflectometer (TDR) soil moisture sensors (SMS) [90], remote sensing of soil moisture stress through the normalized difference vegetation index (NDVI) [91], highly sensitive imagederived canopy indices [92] such as water band index (WBI), a simple visible vegetation index called green-to-red ratio index (GRI) [93], optical signature of leaves including hyperspectral radiometer [94,95] and other systems have been used to measure volumetric water content (VWC) or estimating moisture stress for irrigation scheduling strategies in turfgrass system. Use of soil moisture sensors was found to reduce water usage by 39% as compared to using historical ET data [96].…”
Section: Irrigation Application Methods and Schedulingmentioning
confidence: 99%
“…Considerable efforts have also been made to adapt and incorporate soil moisture measurements into irrigation scheduling on golf courses [97] and optical signatures of leaves [95]. The soil moisture sensor technology adds much promise in to soil-water balance maintenance as well as further implementation of precision irrigation practices and turfgrass management which allows for increased input efficiency by utilizing a site-specific, targeted approach to management [98].…”
Section: Irrigation Application Methods and Schedulingmentioning
confidence: 99%
“…Spectral reflectance measurements were collected in 2010 and 2011 as described in Baker et al (2018 ). The spectroradiometer collected wavelengths from 350 to 2500 nm with a 1.4 nm sampling interval for the visible/NIR spectral region (350 nm – 1000 nm) and 2 nm for the short-wave infrared spectral region (1000 nm – 2500 nm) ( A n et al 2015 ); when interpolated, there is one spectral data point per nanometer, for a total of 2151 spectral data points per measurement. For each replicate plant, 10 measurements were collected and averaged to produce a single measurement ( A n et al 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Hutto et al (2006) Hyperspectral sensors detect critical soil water content 1 day before visual drought symptoms occur with an r 2 of .64 (Dettman- Kruse et al, 2008). An et al (2015) suggested hyperspectral reflectance data can determine the most appropriate wavelengths to determine turfgrass stressors. The water band index measurements from hyperspectral sensors have been reported to exhibit a strong relationship to soil volumetric water content suggesting that the water band index can be used to monitor for turfgrass water stress aside other plant stressors measured by other vegetation indices (Badzmierowski et al, 2019;McCall et al, 2017;Roberson et al, 2021).…”
Section: Remote Sensing Research On Turfgrassmentioning
confidence: 99%